Тріщиностійкість дисперсно-армованого бетону - Турба, Юрій Васильович (Національний університет "Львівська політехніка", 2021)
Дисертаційна робота присвячена питанням підвищення тріщиностійкості цементних бетонів шляхом композиційного полідисперсного армування поліпропіленовими фібрами типу “поліарм” та “мікроарм” для покращення їх міцнісних властивостей і силових та енергетичних характеристик тріщиностійкості. Встановлена ефективність дисперсного армування бетонів транспортного призначення. Показано вплив витрати фібр, відношення довжини фібри до максимального розміру зерен крупного заповнювача, коефіцієнта розсуву зерен крупного заповнювача на міцність на розтяг при згині та характеристики тріщиностійкості дисперсно-армованих цементних бетонів. Розроблено та оптимізовано за критеріями міцності, силових та енергетичних характеристик тріщиностійкості склади цементних бетонів з композиційним полідисперсним армуванням поліпропіленовими фібрами типу “поліарм” та “мікроарм” та доведена їх ефективність. Досліджено деформації зсідання та будівельно-технічні властивості розроблених бетонів. Проведено дослідно-промислове їх впровадження та обгрунтовано техніко-економічну ефективність. Диссертация посвящена вопросам повышения трещиностойкости цементных бетонов путем композиционного полидисперсного армирования полипропиленовыми фибрами типа “полиарм” и “микроарм” для улучшения их прочностных свойств и силовых и энергетических характеристик трещиностойкости. Установлена эффективность дисперсного армирования бетонов транспортного назначения. Показано влияние расходов фибр, отношение длины фибры до максимального размера зерен крупного заполнителя, коэффициента роздвига зерен крупного заполнителя на прочность на растяжение при изгибе и характеристики трещиностойкости дисперсно-армированных цементных бетонов. Разработан и оптимизирован по критериям прочности, силовых и энергетических характеристик трещиностойкости склады цементных бетонов с композиционным полидисперсных армированием полипропиленовыми фибрами типа “полиарм” и “микроарм” и доказана их эффективность. Исследованы деформации усадки и строительно-технические свойства разработанных бетонов. Проведены опытно-промышленное их внедрения и обоснованно технико-экономическую эффективность. The dissertation is devoted to increasing the crack resistance of cement concrete by composite polydisperse reinforcement with polypropylene fibres of "polyreinf" and "microreinf" type to improve their strength properties and strength and energy characteristics of crack resistance. The efficiency of dispersed reinforcement of concrete for transport purposes is established. The introduction substantiates the relevance of the dissertation, formulates the purpose and objectives of the study. The main provisions obtained by the author, which have scientific novelty and practical value, are given. The first section provides a critical review of the literature related to the technological features of concrete reinforced with fibres of different types and types, their impact on physical and mechanical properties, crack resistance and durability, and identifies the theoretical background. The second section presents the characteristics of the source materials and describes the main research methods used in work. The force and energy characteristics of crack resistance of dispersed reinforced concrete were determined using a complete stress-strain diagram during the mechanical tests of concrete prisms. The samples were tested according to the scheme of three-point bending on a 200 ts hydraulic machine. Control samples were loaded until destruction. The third section is devoted to the study of the influence of dispersed reinforcement by different types of fibres with determining the physical and mechanical properties and crack resistance characteristics of concrete. At the first stage, the effect of different fibres on the strength and energy characteristics of crack resistance was studied. The next stage was to optimize the composition of concrete using a three-level three-factor experimental plan and to establish the optimal content of polypropylene fibres such as "polyreinf" and "microreinf". The fourth section presents the results of experimental and statistical modelling of strength properties and crack resistance characteristics of concretes with composite disperse reinforcement with polypropylene fibres such as "polyreinf" and "microreinf". Physico-mechanical, functional properties, shrinkage deformations of concretes of optimal composition with composite disperse reinforcement in comparison with non-reinforced concrete were investigated. The fifth section presents the experimental and industrial implementation results of the developed concretes dispersed and reinforced with polypropylene fibres such as "polyreinf" and "microreinf" for transport purposes. As a result, the dissertation solved a scientific problem with practical significance, namely the development of dispersed reinforced concrete for transport purposes with increased construction and operational properties and crack resistance characteristics. Based on the results of theoretical and experimental studies, general conclusions are formulated.
Трещиностойкость дисперсно-армированного бетона
Crack resistance of dispersedly reinforced concrete
Keywords: дисперсно-армовані бетони; поліпропіленова фібра типу “поліарм” та “мікроарм”; повна діаграма стану; характеристики тріщиностійкості; технологічні фактори; дисперсно-армированные бетоны; полипропиленовая фибра типа “полиарм” и "микроарм"; полная диаграмма состояния; характеристики трещиностойкости; технологические факторы; disperse-reinforced concrete; polypropylene fiber type "polyreinf" and "microreinf"; complete state diagrm; crack resistance characteristics; technological factors; 691.328